Teknik Budidaya Ikan Platy Cendrawasih (Xiphophorus maculatus) - Rudy Wijaya; Kasprijo Kasprijo; Aurelia Rodathul Jannah; Arinal Munah; Desi Fitriani; Fatikha Resya Shabila; Jany Hanna Sabila; Nurul Husnaeny Mustofa; Rien Azizah Mufadhila; Riski Al Gea Fasya Muammar; Wicaksono Rifqi Hartanto; Muh. Sulaiman Dadiono (PT. Gyandharma Global Media, 2025)
Platy fish (Xiphophorus maculatus) is one type of ornamental fish that is popular with the public because it has beautiful colors so that its aesthetic and economic value is high. The purpose of this study was to determine how to cultivate ornamental platy fish (Xiphophorus maculatus) especially the type of cendrawasih platy properly and correctly without aeration starting from spawning to seed care using different seed media, by paying attention to physical and chemical water quality management. There were three treatments used in this study, namely, P1 (Sand + aquatic plants), P2 (sand without plants), and P3 (without sand and without plants). The feeding method was carried out routinely twice a day with add libitum. Water quality monitoring was carried out routinely for three days by measuring the physical and chemical quality of the water. The results showed that the treatment that spawned the most was P1 with a total of 22 fry.